Political markets, the party-related factors and political partyâs market-orientation in Indonesiaâs democracy: evidence from Indonesiaâs 2014 parliamentary election - Ahmad, N. (Springer Science and Business Media B.V., 2022)
Market-orientation has been advanced by political parties in not merely the Western, but also the emerging democracies. Knowledge of the nomenclatures of political markets that emerge in Indonesiaâs democracy, types of political sub-markets considered by Indonesian political partiesâ leaders in Indonesiaâs 2014 parliamentary election and the effects of the party-related factors on perceptions of these partiesâ members and activists regarding the importance of these political markets has, however, been under-developed. Focusing on such issues, this work adopted political marketing perspective and deployed the pure mixed of qualitative and quantitative methods. The findings are as follows. The following political markets evolved in Indonesiaâs democracy. They include the governmental, parliamentary, internal party, electoral and non-electoral and the media markets. In facing such election, most of these partiesâ leaders considered the internal party, media, electorates, competitors and campaign-donors as political sub-markets. These partiesâ members and activists perceived the importance of these political sub-markets. Their perceptions regarding the importance of campaign donors are determined by party ideology and campaign resources. Their perceptions regarding the importance of electorates and party members are instead, influenced by party experience of internal shock. Based on the Indonesian case, this work offers new knowledge of: (1) nomenclatures of political markets that emerge in the emerging democracy; (2) types of political sub-markets considered by political partiesâ leaders in such democracy; and (3) types of the party-related factors that likely determine perceptions of these partiesâ members and activists regarding the importance of these political sub-markets in the parliamentary election. Â© 2021, The Author(s), under exclusive licence to Springer Nature B.V. part of Springer Nature.